1. To simplify this statement we can use the associative law: p∧(q∧r)≡(p∧q)∧r and the idempotent law: p∧p≡p.
So we have:
p∧(p∧q)≡(p∧p)∧q≡p∧q.
2. To simplify this statement we can use the De Morgan's Law: ¬(p∨q)≡¬p∧¬q and the double negation law: ¬¬p≡p.
So we have:
¬(¬p∨q)≡¬¬p∧¬q≡p∧¬q.
3. To simplify this statement we can use the implication law: p→q≡¬p∨q and De Morgan's Law: ¬(p∨q)≡¬p∧¬q and the double negation law: ¬¬p≡p.
So we have:
¬(p⇒¬q)≡¬(¬p∨¬q)≡¬¬p∧¬¬q≡p∧q.
Answer:
- p∧(p∧q)≡p∧q.
- ¬(¬p∨q)≡p∧¬q.
- ¬(p⇒¬q)≡¬(¬p∨¬q)≡¬¬p∧¬¬q≡p∧q.
Comments
Leave a comment